2008
DOI: 10.1038/sc.2008.16
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic bladder dysfunction in patients with motor complete and sensory incomplete spinal cord lesion

Abstract: Patients with somatosensory incomplete lesion of spinal cord seem to have an advantage in the management of neuropathic bladder dysfunction (fewer anticholinergics needed, fewer incontinence episodes and fewer bladder stones).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…This variation was influenced primarily by the neurological level and severity of the SCI. One study 27 reported the incidences for individuals with American Spinal Injury Association Impairment Scale (AIS) A and B to be 15.9% and 21.4%, respectively. However, this study involved individuals with SCI from C4 to T12.…”
Section: Incidence Of Ad During Iatrogenic Urological Proceduresmentioning
confidence: 99%
“…This variation was influenced primarily by the neurological level and severity of the SCI. One study 27 reported the incidences for individuals with American Spinal Injury Association Impairment Scale (AIS) A and B to be 15.9% and 21.4%, respectively. However, this study involved individuals with SCI from C4 to T12.…”
Section: Incidence Of Ad During Iatrogenic Urological Proceduresmentioning
confidence: 99%
“…Aynı çalışmada, düşük mesane kompliyansı olan grupta MCC'nin daha düşük olduğu da bildirilmiştir. Literatürde, OY'li hastalarda mesane boşaltım yöntemini etkileyen faktörleri değerlendiren çok az çalışma mevcuttur (8,26,27). Rapidi Kay nak lar…”
Section: Discussionunclassified
“…Ancak, bazı yazarlar nörolojik ve ürodinamik bulguların her zaman tam korelasyon göstermeyebileceğini bildirmişlerdir (4-7). Çalışmalarda, OY seviyesi ve ciddiyeti ile mesane davranışı arasındaki ilişki üzerinde durulmakta fakat mevcut çalışmaları, farklı değerlendirmelerin kullanılması nedeniyle karşılaştırmak zor olmaktadır (2)(3)(4)(6)(7)(8)(9).…”
Section: öZetunclassified
“…Studies investigating lesion severity and bladder function found no significant difference between complete and incomplete lesions in terms of maximum detrusor pressure and MC (21); mean MC and mean intravesical leak-point pressures were not significantly different between AIS-A and AIS B-E patients (22); although DO was more benign in AIS-B patients than in AIS-A patients, neuropathic bladder type and compliance were not significantly different between AIS-A and AIS-B patients (23). Scivoletto et al (24) have shown that none of the patients with AIS-A impairment on admission reached volitional voiding at 5 months; AIS-B patients had a 90% lower probability of achieving good bladder control and AIS-C patients had 65% lower than AIS-D patients.…”
Section: Discussionmentioning
confidence: 99%